Islamic Personal Development Management in Shaping Religious Attitudes - Alwanto, Alwanto; Suyadi, Suyadi; Waharjani, Waharjani (Early Publishing, 2025)
Islamic religious education in elementary schools faces challenges in shaping the religious character of students in the midst of globalization. This study aims to analyze the management of the Islamic Personal Development Program (BPI), supporting and inhibiting factors, and the collaborative role of stakeholders at SDIT Luqman Al Hakim Yogyakarta. The research uses a qualitative approach with data obtained through observation, interviews, and documentation, then analyzed inductively by triangulation. The results of the study show that BPI management is carried out systematically and sustainably through planning, implementation, evaluation, and supervision functions. The program is implemented in an integrated manner in curricular, co-curricular, and school cultural activities through a halaqah and habituation approach, and is evaluated using mutaba'ah instruments. This program has proven to be effective in increasing students' independence, consistency, and religious awareness. Supporting factors include teacher exemplarity, institutional support, and parental involvement, while barriers include student heterogeneity and variation in teacher competencies.